Effect of irrigation salinity on the growth and yield of two Aus rice cultivars of Bangladesh - Khanam, Tahmina; Akhtar, Nahid; Halim, MA; Hossain, Feroza (Jahangirnagar University Journal of Biological Sciences, 2018)
The experiment was conducted to clarify the growth and yield response of two rice cultivars, BR55 and BR43 under salt stress. Six different concentrations of NaCl viz 50, 100, 150, 200, 250 and 300 mM and distilled water (control) were applied on the rice cultivars which were grown under pot culture condition. Growth parameters like plant height, tiller number, leaf number and leaf area were negatively affected by salinity in both cultivars. Salt stress caused a significant reduction in yield in both cultivars of rice. Growth reduction was higher in BR43 than in BR55.The reduction in yield and yield parameters were found to be lower in BR55 than those in BR43. The results obtained in the present study suggest that BR55 showed higher salt tolerance than in BR43. Jahangirnagar University J. Biol. Sci. 7(2): 1-12, 2018 (December)